Optogenetic stimulation of VTA dopamine neurons reveals that tonic but not phasic patterns of dopamine transmission reduce ethanol self-administration - Bass, Caroline E.; Grinevich, Valentina P.; Gioia, Dominic; Day-Brown, Jon; Bonin, Keith D.; Stuber, Garret D.; Weiner, Jeff L.; Budygin, Evgeny (Frontiers in Behavioral Neuroscience, 2013)
There is compelling evidence that acute ethanol exposure stimulates ventral tegmental area (VTA) dopamine cell activity and that VTA-dependent dopamine release in terminal fields within the nucleus accumbens plays an integral role in the regulation of ethanol drinking behaviors. Unfortunately, due to technical limitations, the specific temporal dynamics linking VTA dopamine cell activation and ethanol self-administration are not known. In fact, establishing a causal link between specific patterns of dopamine transmission and ethanol drinking behaviors has proven elusive. Here, we sought to address these gaps in our knowledge using a newly developed viral-mediated gene delivery strategy to selectively express Channelrhodopsin-2 (ChR2) on dopamine cells in the VTA of wild-type rats. We then used this approach to precisely control VTA dopamine transmission during voluntary ethanol drinking sessions. The results confirmed that ChR2 was selectively expressed on VTA dopamine cells and delivery of blue light pulses to the VTA induced dopamine release in accumbal terminal fields with very high temporal and spatial precision. Brief high frequency VTA stimulation induced phasic patterns of dopamine release in the nucleus accumbens. Lower frequency stimulation, applied for longer periods mimicked tonic increases in accumbal dopamine. Notably, using this optogenetic approach in rats engaged in an intermittent ethanol drinking procedure, we found that tonic, but not phasic, stimulation of VTA dopamine cells selectively attenuated ethanol drinking behaviors. Collectively, these data demonstrate the effectiveness of a novel viral targeting strategy that can be used to restrict opsin expression to dopamine cells in standard outbred animals and provide the first causal evidence demonstrating that tonic activation of VTA dopamine neurons selectively decreases ethanol self-administration behaviors.